KEBIJAKAN PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN BUCKET GUNA MENINGKATKAN KESEJAHTERAAN DI KELURAHAN SITIREJO III - Cut Sah Kha Mei Zsazsa; Ramadha Yanti Parinduri; Boby Indra Prayoga (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2026)
This activity is a community service program focused on government policy regarding community empowerment to improve welfare through "bucket" (gift arrangement) making training in Sitirejo III. The objective of this initiative is to empower the community to enhance their well-being. The training provided to the residents of Sitirejo III covered the creation of flower buckets and snack buckets. The activity involved 35 participants divided into seven groups and was conducted through stages comprising preparation, training and implementation, and evaluation. The results of the training demonstrated a significant improvement. This was evident across various assessed aspects—including awareness, speed, skill, proficiency, innovation capability, and motivation—where scores rose from low levels prior to the training to higher levels afterward. Overall, the bucket-making training made a positive contribution toward empowering the community and improving welfare. However, such outcomes rely on optimal support and motivation derived from government policy in the Sitirejo III Urban Village, as the role of leadership is crucial in determining community welfare. Fortunately, the Sitirejo III Urban Village consistently provides facilities for community empowerment training.